Effects of water quality on growth performance and health of nursery pigs. Issue 1 (15th January 2022) - Lozinski, Brigit M; Frederick, Brent; Li, Yuzhi; Saqui-Salces, Milena; Shurson, Gerald C; Urriola, Pedro E; Wilson, Melissa L; Johnston, Lee J
Abstract: An experiment was conducted to determine the effects of providing drinking water of differing qualities on growth performance and health of nursery pigs. Weanling pigs ( n  = 450; 150 pigs/group; 10 pigs/pen) were assigned randomly to one of three experimental groups consisting of three water sources of varying qualities: 1) Water source A containing 1, 410 ppm hardness (CaCO3 equivalent), 1, 120 ppm sulfates, and 1, 500 ppm total dissolved solids (TDS); 2) Water source B containing 909 ppm hardness (CaCO3 equivalent), 617 ppm sulfates, and 1, 050 ppm TDS; and 3) Water source C containing 235 ppm hardness (CaCO3 equivalent), 2 ppm sulfates, and 348 ppm TDS. Pigs were provided ad libitum access to their respective water sources for the duration of the study which began at weaning (21 d of age) and ended 40 d later (61 d of age). Individual pig weights were recorded weekly along with feed intake on a pen basis. Occurrences of morbidity and mortality were recorded daily. Subjective fecal scores were assigned on a pen basis and blood samples were used to evaluate blood chemistry, cytokine concentrations, and phagocytic activity. A differential sugar absorption test was used to assess intestinal permeability. Fecal grab samples were used to establish diet digestibility, and drinking behavior was video-recorded to assess pigs' acceptance of water sources provided. The statistical model considered fixed effects of water source, room, and their interaction with the random effect of pen. A repeated measures analysis was conducted to determine the effects of water quality over time. There were no differences ( P  > 0.440) among water sources in average daily gain (A, 0.46 kg/d; B, 0.46 kg/d; C, 0.47 kg/d) or average daily feed intake (A, 0.68 kg/d; B, 0.69 kg/d; C, 0.71 kg/d). Overall mortality of pigs was 0.44% and did not differ across the three water sources. There were no differences in apparent total tract digestibility of the diet, intestinal permeability, immune parameters, or blood chemistry attributable to quality of water consumed by pigs. Pigs did not show an aversion to the water sources provided, because total time pigs spent at the drinker did not differ ( P  > 0.750) among water sources on days 1 through 3 of the experiment. These data indicate that the water sources of differing quality studied did not affect growth performance or health of nursery pigs.